Effect of strain rate on plastic deformation bonding behavior of Ni-based superalloys. (1st March 2020) - Zhang, Jian Yang; Xu, Bin; Tariq, Naeem ul Haq; Sun, Ming Yue; Li, Dian Zhong; Li, Yi Yi
Abstract: Plastic deformation bonding (PDB) has emerged as a promising solid state bonding technique with limited risk of phase transformations and residual thermal stresses in the joint. In this study, the PDB behavior of IN718 superalloy was systematically investigated by performing a series of isothermal compression tests at various processing conditions. It was revealed that, with increasing PDB strain rate at 1000 °C, different extents of dynamic recrystallization (DRX) occur in the bonding area of IN718 joints. The extent of DRX, average size of DRXed grains, and a newly proposed "interfacial bonding ratio ( ΨBonding )" parameter (to quantify the bond quality) were initially reduced with increase in the strain rate up to 0.1 s −1 and later increased at further higher strain rates. Electron backscattered diffraction (EBSD) and transmission electron microscopy (TEM) based interfacial microstructure analyses indicated that the quality of the bonded joints is closely related with the development of fine DRXed grains at the bonding interface with the increasing strain, which promotes adiabatic temperature rise. It was revealed that the initial bulging and subsequent migration of the original interfacial grain boundary (IGB) were the main mechanisms promoting DRX in the well bonded IN718 superalloy joints. Moreover, the mechanical properties of the bonded joints were not only controlled by the recrystallized microstructure but also depended upon the Bonding parameter of the joints.